Characterization of plasma membrane proteins in stylosanthes leaves and roots using simplified enrichment method with a nonionic detergent - Yang, Liyun; Gao, Jing; Gao, Mengze; Jiang, Lingyan; Luo, Lijuan (Frontiers in Plant Science, 2022)
Plant plasma membranes (PMs) play an important role in maintaining the stability of the intracellular environment and exchanging information with the external environment. Therefore, deciphering dynamics of PM proteome provides crucial information for elucidating cellular regulation in response to diverse stimuli. In the study, we developed a simplified method for enriching PM proteins in leaf and root tissues of a tropical forage Stylosanthes by combining differential centrifugation and Brij-58 treatment. Both immunoblot analysis and mass spectrometry demonstrated that the representation and abundance of PM proteins were increased in the enrichment fraction, and the contamination of other organellar proteins was decreased. A total of 426 and 388 proteins were predicted to be PM proteins in leaves and roots, respectively. Functional analysis classified these PM proteins into six major categories (transporter, enzyme, receptor, membrane structure protein, vesicular trafficking and chaperone), and orthologs of many PM proteins regulating the responses to abiotic and biotic stresses have been detected. In addition, the sequence analysis, subcellular localization and gene expression analyses of a newly identified receptor-like kinase, SgRKL1, has been performed. Together, these results show that the simplified PM enrichment method can be successfully applied to different plant tissue types and to study the dynamics of PM proteome of Stylosanthes in response to multiple stresses.